2022
DOI: 10.1186/s13071-022-05586-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in abundance and blood meal sources of primary and secondary malaria vectors within Kilombero Valley, Southern Tanzania

Abstract: Background Existing control tools have significantly reduced malaria over the past two decades. However, progress has been stalled due to increased resistance in primary vectors and the increasing role of secondary vectors. This study aimed to investigate the impact of seasonal change on primary and secondary vector abundance and host preference. Understanding the impact of seasonal dynamics of primary and secondary vectors on disease transmission will inform effective strategies for vector man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
2
8
0
Order By: Relevance
“…funestus exhibited a strong preference for human blood meals over other potential hosts such as dogs and chickens. This anthropophilic behavior is consistent with the species known tendencies [35]. In recently study conducted in Kilombero valley in 2022, Katusi et al revealed that, An.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…funestus exhibited a strong preference for human blood meals over other potential hosts such as dogs and chickens. This anthropophilic behavior is consistent with the species known tendencies [35]. In recently study conducted in Kilombero valley in 2022, Katusi et al revealed that, An.…”
Section: Discussionsupporting
confidence: 81%
“…Many houses in the villages prefer to have eave space for air accelerations [42], but in other hands it poses a threat to malaria transmission risks, as mosquitoes are more likely to enter in the house through eave space. Several interventions on house screening have been introduced, this including the idea of eave tube treated with conventional insecticides plus house modification with eave tubes installed with physical barrier inside [42], treated curtains [43] and treated eave ribbons [35, 36], treated chair [46], treated sandals [47], all these tools introduced as structural interventions, in and around the houses, which may impact vector feeding, survivorship, population density and overall vectorial capacity and thus ability to transmit malaria and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies that demonstrated a potential switch in host choice by An. funestus from humans to cattle [ 46 , 47 ]. In brief, given the circumstances of the collections, this observation may be explained by several factors: Firstly, the houses where mosquito collections were conducted had been supplied with intact bed nets before the collections started, which might have created a physical barrier, reducing mosquito exposure to humans [ 48 ]; and forcing mosquitoes to use alternative blood sources in the surrounding areas as previously documented by Iwashita et al [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Myanmar in 2019 indicated that An. minimus demonstrated possible resistance to deltamethrin [ 87 ], however, An. dirus in Thailand was shown to be completely susceptible (100% mortality) to transfluthrin [ 88 ].…”
Section: Discussionmentioning
confidence: 99%